2018
DOI: 10.1038/s41418-018-0079-6
|View full text |Cite|
|
Sign up to set email alerts
|

Post-translational modification of OCT4 in breast cancer tumorigenesis

Abstract: Recurrence and drug resistance of breast cancer are still the main reasons for breast cancer-associated deaths. Cancer stem cell (CSC) model has been proposed as a hypothesis for the lethality of breast cancer. Molecular mechanisms underlying CSC maintenance are still unclear. In this study, we generated mammospheres derived from breast cancer MDA-MB231 cells and MCF7 cells to enrich CSCs and performed DNA microarray analysis. We found that the expression of carboxy terminus of HSP70-interacting protein (CHIP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 43 publications
0
65
0
Order By: Relevance
“…YL-109-induced CHIP upregulation in MDA-MB-231 cells resulted in attenuation of CSC properties, including the mammosphere-forming ability, expression of stemness markers, invasiveness, and metastatic potential [88]. In a similar model, CHIP was found to be significantly downregulated in breast CSCs and such a CHIP deficiency was correlated with mammosphere formation in vitro, lung metastases in xenografted mice, and poor outcome among patients with breast cancer exhibiting low CHIP expression [89]. The authors explained such effects of the CHIP depletion by a failure in CHIP-mediated ubiquitination and degradation of OCT4, a transcription factor promoting stemness that is a client protein of HSP90; in support of that, they demonstrated direct CHIP-OCT4 interactions and also the CHIP depletion-mimicking action of a ubiquitination-defective OKT4 mutant [89].…”
Section: Intracellular Hsp90 and Some Of Its Partners In Chaperoning mentioning
confidence: 91%
See 2 more Smart Citations
“…YL-109-induced CHIP upregulation in MDA-MB-231 cells resulted in attenuation of CSC properties, including the mammosphere-forming ability, expression of stemness markers, invasiveness, and metastatic potential [88]. In a similar model, CHIP was found to be significantly downregulated in breast CSCs and such a CHIP deficiency was correlated with mammosphere formation in vitro, lung metastases in xenografted mice, and poor outcome among patients with breast cancer exhibiting low CHIP expression [89]. The authors explained such effects of the CHIP depletion by a failure in CHIP-mediated ubiquitination and degradation of OCT4, a transcription factor promoting stemness that is a client protein of HSP90; in support of that, they demonstrated direct CHIP-OCT4 interactions and also the CHIP depletion-mimicking action of a ubiquitination-defective OKT4 mutant [89].…”
Section: Intracellular Hsp90 and Some Of Its Partners In Chaperoning mentioning
confidence: 91%
“…Those nestin-HSC71 interrelations seemed to maintain the CSC phenotype and such typical manifestations of the cancer stemness as tumorigenicity, invasion, and spheroid formation. Moreover, alterations in the CHIP expression/activity levels may affect the destiny of some stemness-regulating proteins bound to HSP70 and HSP90, as it was shown for breast CSCs [88,89].…”
Section: Intracellular Hsp70mentioning
confidence: 93%
See 1 more Smart Citation
“…Initial evidence suggests that Oct4 acts as a rheostat gene controlling the development and progression of malignancy in germ cells [6]. More recent evidence reports the expression of Oct4 in somatic malignancies, such as prostate [8], breast [9], ovarian [10], hepatocellular [11], head and neck [12] and cervical [13] cancers. As a cancer marker, Oct4 was recently associated with poor prognosis in hepatocellular carcinomas [14].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have identified post-translational modifications (PTMs) showing aberrant behavior in cancer (8)(9)(10)(11), resulting for instance in abnormal cellular signaling, one of the hallmarks of cancer (12). Phosphorylation of serine, threonine, and tyrosine is one of the most frequent and best studied PTMs (13), and is carried out by different types of protein kinases, consisting mainly of serine/threonine-and tyrosine-specific protein kinases.…”
Section: Introductionmentioning
confidence: 99%